2011
DOI: 10.1523/jneurosci.2002-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Random Noise Stimulation Improves Neuroplasticity in Perceptual Learning

Abstract: Perceptual learning is considered a manifestation of neural plasticity in the human brain. We investigated brain plasticity mechanisms in a learning task using noninvasive transcranial electrical stimulation (tES). We hypothesized that different types of tES would have varying actions on the nervous system, which would result in different efficacies of neural plasticity modulation. Thus, the principal goal of the present study was to verify the possibility of inducing differential plasticity effects using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
335
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 309 publications
(354 citation statements)
references
References 59 publications
18
335
0
1
Order By: Relevance
“…In fact, by using the same PL paradigm (contrast detection) in myopic participants, in a previous study we found that 24 sessions were needed to achieve a VA improvement of 0.16 LogMAR, whereas no improvement in CS was found even with such a long training (Camilleri, Pavan, Ghin, Battaglini, et al, 2014). However, if PL is boosted by the concomitant administration of hf-tRNS as shown by previous studies (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Campana, et al, 2014;Fertonani, et al, 2011;Pirulli, et al, 2013), then 8 sessions of training become enough efficacious to improve uncorrected VA of a similar amount of 24 training sessions with no concurrent stimulation, and to significantly improve uncorrected CS (whereas no improvement was obtained with 24 training sessions using the same paradigm (Camilleri, Pavan, Ghin, Battaglini, et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In fact, by using the same PL paradigm (contrast detection) in myopic participants, in a previous study we found that 24 sessions were needed to achieve a VA improvement of 0.16 LogMAR, whereas no improvement in CS was found even with such a long training (Camilleri, Pavan, Ghin, Battaglini, et al, 2014). However, if PL is boosted by the concomitant administration of hf-tRNS as shown by previous studies (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Campana, et al, 2014;Fertonani, et al, 2011;Pirulli, et al, 2013), then 8 sessions of training become enough efficacious to improve uncorrected VA of a similar amount of 24 training sessions with no concurrent stimulation, and to significantly improve uncorrected CS (whereas no improvement was obtained with 24 training sessions using the same paradigm (Camilleri, Pavan, Ghin, Battaglini, et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…The frequencies ranged from 100 to 640Hz (high frequency range). This stimulation protocol has been demonstrated efficacious in boosting perceptual learning in previous studies (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Fertonani, et al, 2011;Pirulli, et al, 2013). The active electrode had an area of 16 cm 2 and was placed over the occipital cortex measured at ~3 cm above the inion.…”
Section: Transcranial Random Noise Stimulation (Trns)mentioning
confidence: 99%
See 3 more Smart Citations